1993
DOI: 10.1111/j.1530-0277.1993.tb00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol on Kupffer Cell Function

Abstract: Kupffer cells are resident macrophages in the liver and are important in both local and systemic immune responses. We evaluated the ability of Kupffer cells in vitro to respond to immune stimulation after both acute exposure to ethanol and after long-term ethanol consumption of ethanol. Triplets of female Wistar rats were fed a liquid diet containing 0, 12, or 36% ethanol isocalorically for 112 days. When killed, the Kupffer cells were isolated by collagenase perfusion and adhered to plastic 24-well plates. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In rats, no serum specific antibodies can be detected after experimental intragastric or intraportal ovalbumin administration, but an increased IgE or IgG1 specific response is observed when Kupffer cells are blocked with gadolinium chloride prior to antigen administration (81,82). Both advanced liver disease and alcohol impair Kupffer cell function (83). In a study of Kupffer cell phagocytic activity (liver radiocolloid uptake), serum IgE levels and skin prick test reactivity to a battery of food allergens in a group of 52 cirrhotics (27 of them of alcoholic origin), we observed that IgE elevation was restricted to alcoholic cirrhotics, and unrelated to either liver phagocytic function or skin test reactivity to food allergens (32).…”
Section: Antigen Shedding/exposurementioning
confidence: 99%
“…In rats, no serum specific antibodies can be detected after experimental intragastric or intraportal ovalbumin administration, but an increased IgE or IgG1 specific response is observed when Kupffer cells are blocked with gadolinium chloride prior to antigen administration (81,82). Both advanced liver disease and alcohol impair Kupffer cell function (83). In a study of Kupffer cell phagocytic activity (liver radiocolloid uptake), serum IgE levels and skin prick test reactivity to a battery of food allergens in a group of 52 cirrhotics (27 of them of alcoholic origin), we observed that IgE elevation was restricted to alcoholic cirrhotics, and unrelated to either liver phagocytic function or skin test reactivity to food allergens (32).…”
Section: Antigen Shedding/exposurementioning
confidence: 99%